JUAL BELI SATWA LIAR YANG DILINDUNGI DI KECAMATAN GALING KABUPATEN SAMBAS PERSPEKTIF PERATURAN MAHKAMAH AGUNG NOMOR 02 TAHUN 2008 - Rahma Rahma Maulidya; Abu Bakar; Nur Hakimah (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2022)
This research wants to uncover the practice of selling protected wildlife in Galing Sambas and weigh it within the Compilation of Sharia Economic Law (KHES) framework and in the Supreme Court Regulation (Perma) No. 02 of 2008. This research is an empirical juridical law study with a normative approach. It uses primary and secondary data from observation techniques, interviews, and documentation among these study location studies, statutory studies, journals, articles, books - books related to research. Data analysis techniques are through the stage of organizing data, outlining the depth of the units, and doing the synthesis. Whereas in the validity test, the data uses triangulation. The results of this study show two things, namely buying and selling practices and the law. Buying and selling protected wildlife in Galing Sambas District is practiced as usual transactions include; seller, buyer, place of sale and purchase object, settlement, place of sale and purchase, and the expiration of transactions. Payment systems are carried out in cash and non-cash. Such buying and selling practices are fervently legal. At the same time, the law of buying and selling protected wildlife according to KHES is forbidden (haram). These legal differences are due to differences in the assessment between the community and the state of the object of buying and selling, namely protected wildlife. The state provisions on wildlife as stipulated in the Law Number 5 1990 concerning Conservation of Natural Resources and Ecosystems make the conditions for buying and selling in KHES unfulfilled because it is against state law. Keywords: Sale and Purchase, Perma Number 02 of 2008, Protected Wildlife